TINGKAT KEPATUHAN PENGGUNAAN OBAT PADA PASIEN TB PARU DI KLINIK WIRAHUSADA MEDICAL CENTER KOTA MAKASSAR - Tahir, Muhammad; Nurul Izzah (Akademi Farmasi Yamasi Makassar, 2024)
One of the most common infectious diseases in the world is tuberculosis (TB). This disease is caused by the bacterium Mycobacterium tuberculosis. The research conducted included descriptive research using a cross-sectional approach. This study was carried out at Klinik Wirahusada Medical Center in Makassar City in June-July 2023. The population in this study consisted of pulmonary Tuberculosis (TB) patients at Klinik Wirahusada Medical Center in June-July 2023 who were using Anti Tuberculosis Drugs (OAT) for the treatment of pulmonary Tuberculosis (TB) and agreed to participate as respondents. The research sample used all populations (total sampling). Data collection was done using questionnaires by providing written questions to the patients. Data processing was done descriptively, with the data resulting in percentages and calculated by multiplying the respondents' answers by one. 60 respondents were obtained. Out of 60 respondents, 63% were male, and 37% were female. Based on the questionnaire, there were 36 individuals with a high compliance level representing 60%, 15 individuals with a moderate compliance level representing 25%, and 9 individuals with a low compliance level representing 15%.